PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA MATERI STATISTIKA KELAS VI MI MAMBAUL ULUM KELBUNG GALIS BANGKALAN - Nurul Makrifah; Siti Romlah (STIT Al-Ibrohimy Bangkalan, 2023)
The problems that exist in improving student learning outcomes in Mathematics subjects in class VI MI Mambaul Ulum Kelbung are students' passive response and students' interest in learning in Mathematics subjects is low and students have the perception that Mathematics is a difficult subject to learn so that in When learning takes place, students pay less attention to explanations from educators, causing low student learning outcomes. Therefore, the formulation of the problem in this research is